Retreatment of a choroidal vein of Galen malformation with embolization 42 years after open surgical treatment in the neonatal period. (8th October 2016) - Elijovich, Lucas; Choudhri, Asim F; Arthur, Adam S; Klimo, Paul; Boop, Frederick A; Berenstein, Alejandro
Abstract : In 1976 an infant boy initially presented with a choroidal vein of Galen malformation (cVOGM). Craniotomy and clipping of the anterior cerebral artery and posterior choroidal arteries was performed, which was reported in the literature 40 years ago. The patient remained asymptomatic until age 42 when he re-presented with an isolated intraventricular hemorrhage. Angiography demonstrated cVOGM with venous sinus occlusive disease leading to venous hypertension and subsequent intraventricular hemorrhage. The angiogram also demonstrated a 'pseudo-nidus' composed of multiple arterial-to-arterial anastomoses that had developed as a result of the original surgical treatment. We embolized a portion of the lesion to reduce the venous hypertension. The patient has been asymptomatic for more than 2 years. To our knowledge, this is the first reported case of a symptomatic neonatal VOGM treated with open surgery that required embolization as an adult for a delayed hemorrhagic presentation.